MicroRNA as a Potential Diagnostic and Prognostic Biomarker in Diffuse Large B‐Cell Lymphoma: A Systematic Review and Meta‐Analysis - Shaghayegh Khanmohammadi; Mahdi Masrour; Parisa Fallahtafti; Fatemeh Hasani (Cancer Reports)
ABSTRACT Background Recently, microRNAs (miRNAs) have been applied as biomarkers for diffuse large B‐cell lymphoma (DLBCL) patients. Early diagnosis and management of DLBCL can improve patient survival and prognosis. Aims This systematic review and meta‐analysis aimed to evaluate the diagnostic and prognostic accuracy of miRNA biomarkers in DLBCL patients. Methods We used the keywords “diffuse large B‐cell lymphoma” and “microRNA” to search databases for original publications until June 14, 2023. Specificity, sensitivity, and AUC were used to assess diagnostic accuracy, and the prognostic value was assessed using the overall survival (OS) and progression‐free survival (PFS) hazard ratio (HR). A subgroup analysis was performed based on the sample type acquired to investigate the heterogeneity. Results Thirteen diagnostic and 33 prognostic studies were included from 839 articles. The Reitsma bivariate model estimated a sensitivity of 0.788 (95% CI: 0.733–0.834, p < 0.001), a specificity of 0.727 (95% CI: 0.654–0.790, p < 0.001), and an AUC of 0.824 in. The pooled AUC was 0.7385 (95% CI: 0.6847–0.7923, p < 0.0001). The pooled OS and PFS HRs (> 1) were 2.2847 (95% CI: 1.7248–3.0263, p < 0.0001) and 2.4883 (95% CI: 1.7367–3.5650, p < 0.0001). The pooled OS and PFS HRs (< 1) were 0.4965 (95% CI: 0.3576–0.6894, p < 0.0001) and 2.4883 (95% CI: 1.7367–3.5650, p < 0.0001). MiR‐155 diagnostic values had a sensitivity of 0.710 (p > 0.1) and a specificity of 0.725 (p < 0.05), with an AUC of 0.776. miR‐21 diagnostic values had an AUC of 0.8468 (p < 0.0001) and OS HR of 2.8938. Conclusion MicroRNAs could serve as a powerful diagnostic and prognostic tool in DLBCL.